The Role of Maqāṣid Al-Sharī‘ah in Promoting Sustainable Development: A Study Within Islamic Legal Framework - Muhammadong Muhammadong (Jurnal Budi Pekerti Agama Islam, 2025)
Sustainable development is now a very important worldwide issue since it is important for the health of future generations without harming the environment or generating social injustice. In this context, the Maqāṣid al-Syarī‘ah method can provide an essential foundation for fostering sustainable development, grounded in the principles of Islamic law. This study seeks to examine the correlation between Maqāṣid al-Syarī‘ah and sustainable development through the lens of Islamic law. The methodology employed is a literature research utilizing a normative-qualitative approach, examining both primary and secondary texts pertinent to Islamic law and Maqāṣid al-Syarī‘ah. The study's findings indicate that Maqāṣid al-Syarī‘ah, which emphasizes the safeguarding of religion, life, intellect, lineage, and wealth, corresponds with the objectives of sustainable development, including social justice, environmental conservation, and economic empowerment. Further debate indicates that the incorporation of Maqāṣid al-Syarī‘ah principles into sustainable development strategies can establish an equilibrium between economic advancement and the safeguarding of human rights and the environment. In conclusion, the implementation of Maqāṣid al-Syarī‘ah in sustainable development can fortify a just and enduring legal framework and offer a resolution to the contemporary global difficulties confronting the world.